2020
DOI: 10.18488/journal.1.2020.103.159.170
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parental Reading Socialisation on the Reading Skill Performance of Rural Primary School Students in Sarawak

Abstract: Extant research on home literacy practices such as parental reading socialisation have demonstrated positive impacts on children in terms of academic performance. A particular aspect that sparks pedagogic importance is the scaffolding potential of reading at home to the learning of English language in non-native English Language contexts. This study aimed to examine the effects of mother's involvement in homereading sessions on students' English reading skill performance in Bau, Sarawak. Prior to carrying out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…reading performance (Raslie et al, 2020). Therefore, parents needed to be further guided to fully utilize the reading activities for more significant outcomes in children's ESL learning.…”
Section: Discussion and Implications Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…reading performance (Raslie et al, 2020). Therefore, parents needed to be further guided to fully utilize the reading activities for more significant outcomes in children's ESL learning.…”
Section: Discussion and Implications Of The Studymentioning
confidence: 99%
“…Emerson et al (2012) also stated that parental involvement in children's ESL learning can improve children's development in term of motivation, affection, social and cognitive. Specific types of parental involvement such as reading activities have also contributed a positive impact on children's ESL reading (Raslie, Deli, John, Mikeng, & Pandian, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, Ramalingam, Maniam, and Karuppanan [10] identify a significant relationship between achievements of students and parental involvement, namely in the aspects of at home learning, parenting, making decisions and volunteering. Besides that, Raslie et al [11] revealed a positive relationship between the way parents get involved with their children in home literacy and students' academic achievement despite the low level of involvement.…”
Section: Research Question 2: the Influence Of Parental Involvement O...mentioning
confidence: 99%
“…Raslie et al [11] reported a low level of involvement when the frequency of mother-child shared reading sessions was found to be generally low. Majority of the participating mothers attended primary school and high school.…”
Section: Low Level Of Involvementmentioning
confidence: 99%
See 1 more Smart Citation